Dampak Implementasi Lawfull Interception pada Pemberantasan Tindak Pidana Terorisme - Ade Mulya; Marzuki Ismail; R. Bayu Yuliantoro; Heriyanto Kandati (Formosa Journal of Multidisciplinary Research, 2022)
The terrorism is crime categorized as a serious threat that requires speed of handling with the support of access to accurate and fast information. The Lawful Interception approach that has been accommodated in the latest revised terrorism law has made an important contribution. This is a new way to speed up the investigation of criminal acts of terrorism. The research was conducted qualitatively by studying literature and in-depth interviews with 3 informants. The research focus on law enforcement for criminal acts of terrorism in Indonesia. The results of the research study state that the impact of Lawful Interception has a significant influence in assisting the process of disclosure and investigation of criminal acts of terrorism. However, there is a need for oversight and procedures to guard against potential breaches of privacy.